Avaliação da eficiência na geração de energia elétrica de um motor híbrido (combustão + ar comprimido) a partir de testes em protótipo real - Gasparini Croce, Rodrigo; Dariva, Antônio; Pereira Trarbach, Emerson; Arthur Firmino Monhol, Filipe (Latin American Journal of Energy Research, 2021)
The continuous research for high efficiency and low emission engines are the technological challenges nowadays. Internal combustion engines are widely used due to low-cost if compared to the electrical vehicles' propulsion systems. Unfortunately, internal combustion engines have low efficiency; about 20%-25% are converted to mechanical power. A new hybrid approach engine running on ethanol and compressed air is presented in this paper. As a result, the global engine efficiency is improved once a part of energy comes from compressed air stored in an external reservoir. By measuring the ethanol consumption and the compressed air flux is possible to calculate the global engine efficiency when it runs a stationary electric generator connected to a known load. This paper presents a conceptual working flow of an Internal Combustion Engine and a Hybrid Engine but focused to the prototype developed. The test procedures and results are shown and the potential to apply this new concept in a vehicle.